The effect of Gestalt therapy on generalized anxiety disorder and test anxiety in students - hosein keshavarz; m h; s gh (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2016)
The Present study is a single subject study. Purpose of the study was to investigate effectiveness of gestalt therapy on generalized anxiety disorder and test anxiety with college students. Participants were recruited through posting on the local university campus. 5 individuals enrolled in the study. All individuals met criteria for generalized anxiety disorder (GAD) based on DSM-IV-TR and test anxiety by psychologist of counseling center of university. The effectiveness of Gestalt therapy for generalized anxiety disorder (GAD) and test anxiety was evaluated in a baseline across post-treatment and follow-up. Self-report of GAD and test anxiety showed that four of the five participants reached low levels of GAD and test anxiety by post-treatment. Results support the construction of comprehensive gestalt therapy protocols for generalized anxiety disorder and test anxiety. Self-report of GAD and test anxiety showed that four of the five participants reached low levels of GAD and test anxiety by post-treatment. Results support the construction of comprehensive gestalt therapy protocols for generalized anxiety disorder and test anxiety.